2002
DOI: 10.1103/physrevlett.88.122302
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Soft Nuclear Bremsstrahlung in Proton-Nucleus Collisions

Abstract: Photon energy spectra up to the kinematic limit have been measured in 190 MeV proton reactions with light and heavy nuclei to investigate the influence of the multiple-scattering process on the photon production. Relative to the predictions of models based on a quasifree production mechanism, a strong suppression of bremsstrahlung is observed in the low-energy region of the photon spectrum. We attribute this effect to the interference of photon amplitudes due to multiple scattering of nucleons in the nuclear m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 29 publications
8
48
0
Order By: Relevance
“…The authors of [6,9] clearly observed the hump-shaped plateau in the experimental spectrum which is different from the typical exponential shape of the bremsstrahlung spectra previously measured by Edington and Rose in [1]. The further careful measurements of the bremsstrahlung emission in the proton nucleus scattering were done by the TAPS collaboration [11] and results confirmed the clear presence of such a plateau in the spectra. A supposition to explain such behavior of the spectra is to consider the internal dynamic motion of nucleons and collisions between them.…”
Section: Introductionsupporting
confidence: 50%
See 4 more Smart Citations
“…The authors of [6,9] clearly observed the hump-shaped plateau in the experimental spectrum which is different from the typical exponential shape of the bremsstrahlung spectra previously measured by Edington and Rose in [1]. The further careful measurements of the bremsstrahlung emission in the proton nucleus scattering were done by the TAPS collaboration [11] and results confirmed the clear presence of such a plateau in the spectra. A supposition to explain such behavior of the spectra is to consider the internal dynamic motion of nucleons and collisions between them.…”
Section: Introductionsupporting
confidence: 50%
“…In Fig. 7 we add our calculations of the bremsstrahlung spectra for p + 58 Ni (a) and p + 107 Ag (b) at E p = 190 MeV in comparison with experimental data [11] which are normalized on the geometrical cross section σ r = 1.44 πA 2/3 fm 2 with A the target mass number (see Fig. 1 in [11] for the data and text in that paper for details).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations